Species identification and generic diversity analysis by DNA fingerprinting of yeast isolates from Philippine rice wine starters - Lim, Elaine Anne Y. (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2006)
In the Philippines, considerable variation in rice wine quality is often obtained between and among rice wine producers. Microbial composition of rice wine starter is critical to maintaining the quality of wine. To better understand the microbial ecology, yeast strains were isolated from starters obtained from three areas in Ifugao province for morphological and molecular characterization. DNA analysis was done using modified RAPD using 20-mer Seoulin Research Institute Life Science (SRILS) Uniprimers. Three of the 12 SRILS primers were found to have the highest level of polymorphism of DNA bands among the yeast isolates. SRILS 1 was the most discriminatory primer, differentiating between closely related Saccharomyces cerivisiae strains 2103 and 2104. With SRILS 9 , isolate K2 from Kiangan showed identical pattern with Hansenula anomala strain 2063, while both SRILS 6 and 9 revealed that isolates B3 from Banawe and K3 were very similar to Saccharomycopsis fibuligera strains 2076, 2077, 2081 and 2109. The unknown isolates and the corresponding genetically similar reference strains also showed comparable morphological characteristics. These results demonstrate the utility of RAPD and SRILS primers in yeast species identification and classification and present a major step toward achieving a better control of starter constitution and rice wine quality.